2019
DOI: 10.28991/cej-2019-03091422
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Powder Concrete with Steel, Glass and Polypropylene Fibers as a Repair Material

Abstract: Repairing of reinforced concrete structures is currently a major challenge in the construction industry and is being put back into operation with a slight loss in load carrying capacity. Damage occurs due to many factors that reduce the strength of concrete structures and their durability. The aim of this paper is study the compatibility between three types of reactive powder concrete with (steel fibre, glass fibre and polypropylene fibre) as a repair materials and normal strength concrete as a substrate concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Basalt fibres which also have the capacity of being non corrosive have been proved to impart high flexural and compressive strength up to 120 MPa along with good durability properties [12]. RPC has been customized to be used as a repair material with glass fibres and it has proved to have good binding strength with the old concrete substrate [13]. Apart from the type of fibres the size of the fibres based on aspect ratio plays a major role in determining the properties of RPC and researchers have extensively worked on studying the behaviour of RPC with different size fraction of fibres [14].…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fibres which also have the capacity of being non corrosive have been proved to impart high flexural and compressive strength up to 120 MPa along with good durability properties [12]. RPC has been customized to be used as a repair material with glass fibres and it has proved to have good binding strength with the old concrete substrate [13]. Apart from the type of fibres the size of the fibres based on aspect ratio plays a major role in determining the properties of RPC and researchers have extensively worked on studying the behaviour of RPC with different size fraction of fibres [14].…”
Section: Introductionmentioning
confidence: 99%
“…The different types of additives such as rubber, steel, glass and polypropylene fibers were added into concrete to improve the strength and toughness (Liu et al, 2019). Salim et al (2019) explored that the bond strength between the reactive powder concrete with glass fiber as a repair material and the normal strength concrete as a substrate layer is relatively high when compared to the concrete having steel and polypropylene fibers. Kadam et al (2019) found that increasing the percentage of fiber volume, the compressive and flexural strength also increases.…”
mentioning
confidence: 99%